Chapter 12. Onion, Leek, and Chive Production - Johan Desaeger; Peter J. Dittmar; ¨Pamela Roberts; Xavier Martini; Shouan Zhang; Lincoln Zotarelli (EDIS)
Chapter 12 of the Vegetable Production Handbook of Florida